Comparisons of the pharmacokinetics and tolerability of fixed-dose combinations of amlodipine besylate/losartan and amlodipine camsylate/losartan in healthy subjects: a randomized, open-label, single-dose, two-period, two-sequence crossover study - Choi Y; Lee S; Cho SM; Kang WH; Nam KY; Jang IJ; Yu KS (Dove Medical Press, 2016)
YoonJung Choi,1 SeungHwan Lee,2 Sang-Min Cho,3 Won-Ho Kang,3 Kyu-Yeol Nam,4 In-Jin Jang,1 Kyung-Sang Yu1 1Department of Clinical Pharmacology and Therapeutics, Seoul National University College of Medicine, 2Clinical Trials Center, Seoul National University Hospital, 3Research Institute, 4Global R&D, Korea United Pharm Inc., Seoul, Republic of Korea Background: A fixed-dose combination (FDC) of amlodipine and losartan has been used to reduce blood pressure in patients whose hypertension is not sufficiently controlled with either drug alone. The aim of this study was to evaluate the pharmacokinetic (PK) characteristics and tolerability of an FDC of 6.94 mg amlodipine besylate (5 mg as amlodipine)/50 mg losartan potassium compared to an FDC of 5 mg amlodipine camsylate/50 mg losartan potassium in healthy subjects. Subjects and methods: A randomized, open-label, single-dose, two-period, two-sequence crossover study was conducted on 46 healthy male subjects. Blood concentrations were measured by liquid chromatography–tandem mass spectrometry. Blood samples were collected up to 144 hours post dose for each period. PK parameters were calculated in each treatment group using a noncompartmental method. The 90% confidence intervals (CIs) of the geometric mean ratios of the two treatments for the maximum plasma concentration (Cmax) and the area under the concentration curve from time zero to the last quantifiable time point (AUC0–t) were estimated. Tolerability assessments were performed for all subjects who received the drug at least once. Results: The PK profiles of the two treatments were similar. For amlodipine, the geometric mean ratios (90% CIs) of amlodipine besylate to amlodipine camsylate for the Cmax and AUC0–t were 0.98 (0.94-1.01) and 0.97 (0.93-1.01), respectively. The corresponding values for losartan were 0.91 (0.81-1.02) and 1.05 (0.98-1.12), respectively. The incidence of adverse events was not significantly different between the two treatments, and both were well tolerated. Conclusion: An FDC of 6.94 mg amlodipine besylate (5 mg as amlodipine)/50 mg losartan potassium produced similar results to an FDC of 5 mg amlodipine camsylate/50 mg losartan potassium treatment with respect to the PK parameters of amlodipine and losartan based on Cmax and AUC0–t values. The amlodipine besylate/losartan potassium combination was well tolerated by healthy male subjects. Keywords: comparative pharmacokinetics, amlodipine, losartan, drug development